Heterogeneity of the "Classical" Antithrombin III Deficiency - Sas, Géza; Petö, Iván; Bánhegyi, Denes; Blaskó, György; Domján, Gyula (Thrombosis and Haemostasis, 1980)
We investigated two thrombophilia families with the "classical" type of antithrombin III deficiency, i.e., with a low antithrombin III level measured both by immunochemical and functional methods.We obtained different antithrombin III patterns in the plasma of the affected members of the two families with the modified two dimensional immunoelectrophoresis method (heparin in agarose). In one family, the electrophoretic mobility of the antithrombin III is identical with that of normal antithrombin III. In the other, the antithrombin III displayed a decreased electrophoretic mobility in the heparinized agarose gel. The relatively low affinity of this antithrombin III to heparin could be directly proved by the heparin-agarose affinity chromatography, too. These two different antithrombin III patterns were observed by other investigators at different families as well.On the basis of our simultaneous observations of these two families we propose a classification of the inherited congenital antithrombin III deficiencies.
Keywords: Inherited AT-III deficiency; Heterogeneity